Pendampingan Kamus Bahasa Inggris Berbasis Aplikasi Sebagai Media Pembelajaran di MTS Diniyyah - Missi Tri Astuti; Cyintia Kumalasari; Octadino Haryadi; M. Rizki Fadhilah; Roiyatul Ruqayah; Esti Raihana (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
This community service activity is a service which explains and teaches how to use an electronic English dictionary application from free to paid. The targets of this service are teachers and students of MTS Diniyah Putri. The method used in carrying out this community service is the method of preparation, implementation and monitoring of what has been explained to find out how far the PKM participants understand the use of the English electronic dictionary application This. This application media can be one of the media that can increase motivation so that learning English becomes more effective and efficient so that the results obtained are maximized.